PERANAN GOOD CORPORATE GOVERNANCE (GCG) TERHADAP PENCEGAHAN FRAUD - Anisa Putri; Elsaty, Diva Fara; Fadhilah, Parras Intan; Devi, Selvia Kali; Supraja, Galih (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
Fraud poses a serious threat to organizational sustainability, causing financial losses, damaging reputation, and undermining public trust. Good Corporate Governance (GCG) is recognized as an effective strategy to prevent fraud by implementing principles such as transparency, accountability, responsibility, independence, and fairness. This study aims to examine the role of GCG in fraud prevention by analyzing literature from journals covering various sectors, including banking, healthcare, and Islamic institutions. The analysis reveals that in the financial sector, the implementation of GCG integrated with internal audits and internal control systems has a significant impact on preventing fraud. Conversely, in the healthcare and Islamic institution sectors, the influence of GCG tends to be weaker due to inadequate internal oversight, low individual morality, and a lack of structural support. These findings highlight that the effectiveness of GCG in fraud prevention depends on consistent implementation, integration with internal control systems, and strengthening organizational culture and individual morality. This study recommends optimizing GCG through stricter internal oversight, enhanced audit capacity, and fostering an organizational culture that supports good governance. With a more holistic approach, GCG can serve as a cornerstone in creating transparent, accountable, and fraud-free organizations